2020
DOI: 10.1111/pan.13931
|View full text |Cite
|
Sign up to set email alerts
|

I'm afraid! Children's experiences of being anesthetized

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…By the way, majority of parents of those preschoolers prefer withholding surgical and anesthetic information from their kids for the fears of children’s anxiety and stress induced by potential upcoming surgery and anesthesia. As results, children in this subgroup are psychologically underprepared prior to operating room (OR) [ 7 ]. Accordingly, most of these children were likely to develop anxiety when they cognitively perceived that their body would go through some kinds of manipulation under surgical knife when they are forced to put under deep sleep.…”
Section: Introductionmentioning
confidence: 99%
“…By the way, majority of parents of those preschoolers prefer withholding surgical and anesthetic information from their kids for the fears of children’s anxiety and stress induced by potential upcoming surgery and anesthesia. As results, children in this subgroup are psychologically underprepared prior to operating room (OR) [ 7 ]. Accordingly, most of these children were likely to develop anxiety when they cognitively perceived that their body would go through some kinds of manipulation under surgical knife when they are forced to put under deep sleep.…”
Section: Introductionmentioning
confidence: 99%
“…It could be that parents and children have different causes of anxiety. Parents may be more worried about the surgical outcomes, anesthesia-related side effects and potential complications, while the picture book we used couldn't answer those questions [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Positive feelings toward being present (14) "It was good for me, now my heart is a bit better" (Interview 10). "I was happy to go inside, it changed my mindset about theatre" (Interview 12).…”
Section: Theme: a Positive Experiencementioning
confidence: 99%
“…From the child's perspective, several studies demonstrated that children think the presence of their caregivers during induction of anesthesia reduce their own anxiety. 14,15 Research from the African continent is limited. 16 SA is a country rich in diversity and culture, where multiple ethnic groups, speaking different languages coexist.…”
mentioning
confidence: 99%